Analysis of magnetization transfer (MT) influence on quantitative mapping of T2 relaxation time. Issue 1 (12th March 2019) - Radunsky, Dvir; Blumenfeld‐Katzir, Tamar; Volovyk, Osnat; Tal, Assaf; Barazany, Daniel; Tsarfaty, Galia; Ben‐Eliezer, Noam
Abstract : Purpose: Multi‐echo spin‐echo (MESE) protocol is the most effective tool for mapping T2 relaxation in vivo. Still, MESE extensive use of radiofrequency pulses causes magnetization transfer (MT)‐related bias of the water signal, instigated by the presence of macromolecules (MMP). Here, we analyze the effects of MT on MESE signal, alongside their impact on quantitative T2 measurements. Methods: Study used 3 models: in vitro urea phantom, ex vivo horse brain, and in vivo human brain. MT ratio (MTR) was measured between single‐SE and MESE protocols under different scan settings including varying echo train lengths, number of slices, and inter‐slice gap. MTR and T2 values were extracted for each model and protocol. Results: MT interactions biased MESE signals, and in certain settings, the corresponding T2 values. T2 underestimation of up to 4.3% was found versus single‐SE values in vitro and up to 13.8% ex vivo, correlating with the MMP content. T2 bias originated from intra‐slice saturation of the MMP, rather than from indirect saturation in multi‐slice acquisitions. MT‐related signal attenuation was caused by slice crosstalk and/or partial T1 recovery, whereas smaller contribution was caused by MMP interactions. Inter‐slice gap had a similar effect on in vivo MTR (21.2%), in comparison to increasing the number of slices (18.9%). Conclusions: MT influences MESE protocols either by uniformly attenuating the entire echo train or by cumulatively attenuating the signal along the train. Although both processes depend on scan settings and MMP content, only the latter will cause underestimation of T2 .